Analysis of Criminal Law Policy on Sexual Violence and Legal Protection for Victims of Sexual Violence - Suwandi Siregar; Nelvitia Purba (ISNU Sumatera Utara, 2025)
Sexual violence is a form of crime that has a multidimensional impact on victims, both physically, psychologically, socially, and legally. So far, the regulation of sexual violence crimes in Indonesia tends to be partial and morality-oriented, as reflected in the Criminal Code (KUHP). This condition causes protection for victims to be not optimal. The presence of Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law) is an important milestone in the reform of criminal law policies that are more comprehensive and victim-perspective-oriented. This study aims to analyze criminal law policy against sexual violence crimes in Indonesia and examine the form of legal protection for victims of sexual violence from the perspective of the TPKS Law. The research method used is normative legal research with a legislative approach. Research data was obtained through literature studies by analyzing primary, secondary, and tertiary legal materials, which were then analyzed qualitatively. The results of the study show that Indonesia's criminal law policy has undergone a paradigm shift from a moral approach to a human rights-based approach through the TPKS Law as a lex specialis. The TPKS Law regulates various forms of sexual violence more broadly and ensures victim protection through protection, handling, and recovery mechanisms. However, the implementation of the TPKS Law still faces obstacles, especially related to incomplete implementing regulations, limited understanding of law enforcement officials, and weak coordination in the integrated criminal justice system. This study concludes that although the TPKS Law is a significant advance in the protection of victims of sexual violence, its effectiveness is highly dependent on strengthening the legal structure and culture in order to be able to realize substantive justice for victims.